Messages of parents affection for children in the movie bulan terbelah di langit amerika - Muhammad Ikhsan Jati Kusuma (International Journal of Communication and Society, 2019)
This study aims to explain how the message of peace and what peace messages are featured in the film. This type of research is qualitative. Researchers analyze the signs that appear in the drawings and dialogue using semiotic analysis of Charles Sander Pierce model, as well as classify in Pierce type of icons, indexes, and symbols. The result of this research is that to the filmmakers, researchers hope that every production of films should consider the interests of the wider community, not only about idealism alone should pay attention to the nature of the media itself, namely informative, educative, and also entertaining As modeled after the Bulan terbelah di Langit Amerika